Kesesuaian dimensi kursi terhadap data antropometri anak sekolah dasar di Jakarta Utara - Hiromi Hiromi; Yunisa Astiarani; Robi Irawan; Mariani Santosa (Fakultas Kedokteran Universitas Trisakti, 2021)
BACKGROUND In Indonesia, primary school begins at 6 years old and continues until 12, where most of their growth is experienced at that age. Non-ergonomic school furniture can harm the musculoskeletal system. This study evaluates the suitability of chair dimensions to elementary school student’s anthropometry in North Jakarta. METHODSA cross-sectional study of 98 students in North Jakarta. Chair dimension data and student anthropometry were measured using a tape measure, which was then analyzed using the Chi-Square Goodness of Fit Test to evaluate their suitability. RESULTSThe ages of the students ranged from 5 to 11 years. Anthropometric measurements of students show that the mean Sitting Shoulder Height is 41.81±4.36 cm, Popliteal Height 36.83±3.77 cm, Hip Breadth 25.88±3.47 cm, and Buttock-Popliteal Length 36.56±4.33 cm. While the average size assessed from the seat dimensions is Seat Height 41.71±0.22 cm, Seat Width 37.2±1.26 cm, Seat Depth 37.2±1.42 cm, and Backrest Height Above Seat 35.54±3.19 cm. The results of Goodness of Fit with Kendall's Tau-b critical value for the suitability of chair dimensions to student anthropometry were 0.37, and vice versa 0.672, which stated a discrepancy. CONCLUSIONThere is a mismatch between chair dimension and anthropometry of elementary school students in North Jakarta. Adjustment of chair dimensions needs to be done using a student's average size approach to prevent musculoskeletal disorders.